Current trends of Kazakhstani tourism industry development: the opinion of domestic companies (Journal of Economic Research & Business Administration, 2015)
Around the world tourism shows the higher growth rates and significantly improves the population living conditions and country’s sustainable development. The monetary receipts into the country increasedand new workplaces created due to the tourism. In Kazakhstan a tourism is in its infancy stage. Rich natural resources, historical monuments and showplaces predicting the confident future under conditions of higher competitiveness on the global tourist market. However, difficulties, appeared at present stage, complicated the entire development process. This article considered the achievements of Kazakhstan’s tourism industry according to The Travel & Tourism Competitiveness Index, given a statistical overview of country’s tourism development. Along with the success, the problems identified using qualitative methods of sociological research – in-depth interview are given. Series of in-depth interviews with tourist companies top managers curried out within the research project «Formation of the «Kazakhstan» country brand in terms of country innovative development», funded by the Ministry of Education and Science of the Republic of Kazakhstan. Survey respondents accessed the development of tourism industry development and made recommendations for its further development
Keywords: The Worldwide Tourist Organization of United nations; The Travel & Tourism Competitiveness Index; domestic tourists; foreign tourists; foreign guests; Kazakhstani tourist organization